PERAN HARGA DAN PROMOSI TERHADAP MINAT BELI BUKU "MENJADI MANUSIA BERKARAKTER" - Helen Veranika; Neng Silvi Miladiah; Ati Yulyanti; Wulan Meliyawati; Ipan Ipan; Surya Alam (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study investigates the role of price and promotion on the purchase intention of the book "Becoming a Characterful Human." The study employed a qualitative approach with a descriptive case study design. Fifteen potential buyers were interviewed using semi-structured interviews to gather data on their perceptions of the book's price, the effectiveness of the promotion strategies used, and the factors influencing their purchasing decisions. The results showed that while the promotion strategies were effective in raising awareness and generating interest, the relatively high price of the book posed a significant barrier to purchase. The study concluded that the publisher needs to consider adjusting the price, offering more attractive sales packages, or strengthening promotion strategies to highlight the book's value and reduce price barriers for consumers. By balancing effective promotion strategies with a more competitive price, the publisher can maximize the book's sales potential